United Arab Emirates : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that the United Arab Emirates has continued to benefit from its perceived safe-haven status amid regional instability. The economic recovery has been solid, supported by the tourism and hospitality sectors, and a rebounding real estate sector. Although growth in oil production moderated, public projects in Abu Dhabi and buoyant growth in Dubai's service sectors continued to underpin growth, which reached 5.2 percent in 2013. The macroeconomic outlook is positive. Economic growth is expected at 4.8 percent in 2014 and about 4.5 percent in coming years, supported by a number of mega projects announced and the successful bid for the World Expo 2020.